Endovascular embolization strategy for renal arteriovenous malformations. (February 2014) - Murata, Satoru; Onozawa, Shiro; Nakazawa, Ken; Akiba, Ayako; Mine, Takahiko; Ueda, Tatsuo; Yasui, Daisuke; Sugihara, Fumie; Kondoh, Yukihiro; Kumita, Shin-ichiro
Background: Renal arteriovenous malformations (AVMs) are rare vascular malformations that cause hematuria. Treatment for renal AVMs has evolved from open nephrectomy to transcatheter arterial embolization (TAE). Purpose: To retrospectively evaluate efficacy and adverse events of TAE for renal AVMs. Material and Methods: We examined 12 patients (three men, nine women; mean age, 56 years) with renal AVM with gross hematuria, who underwent 14 sessions of treatment, using various embolization materials (liquid embolization agents, gelatin sponge, and coils). Among the 12 patients, 10 had cirsoid AVMs, eight of which were high-flow lesions. The remaining two patients had aneurismal AVMs. We assessed technical and clinical success, and also complications. All patients were followed for 7–92 months (mean, 48 months). Results: Technical success was obtained in all patients. Primary clinical success was obtained in all patients; however, recurrence was observed in two patients who were treated with coils alone. A second session of TAE led to the sustained relief of symptoms. Clinical success rate was significant better ( P = 0.045) when coils combined with other agents or liquid agents were used, than when only coils were used. No major complications occurred in any of patients; post-embolization syndrome and deterioration of renal function were not observed. Conclusion: TAE treatment was safe, effective, and provided a good outcome, except when only coils were used as the embolization agent.